Indigene's lands in the Colonial Legislation (Revista da Faculdade de Direito, Universidade de São Paulo, 2000)
This article analizes some of the questions implied in the legal recognition of native land rights in Colonial Brazil. It considers specially how the advance of colonization meant, in practical terms, the loss, by the Indians, of their land rights, which were never denied by the laws.